High-Performance Work Practices and Employee Wellbeing—Does Health-Oriented Leadership Make a Difference? - Hauff, Sven; Krick, Annika; Klebe, Laura; Felfe, Jörg (Frontiers in Psychology, 2022)
This paper sheds further light on the contextual boundaries in the relationship between high-performance work practices (HPWPs) and employee wellbeing. In particular, we analyze whether this relationship is moderated by health-oriented leadership behavior (i.e., staff care) which describes the extent to which leaders value, are aware of, and protect their followers’ health at work. Our analyses are based on employee data (N = 1,345) from Germany, covering two points in time. Findings show positive associations between HPWPs and happiness-related (i.e., engagement, commitment) and health-related (i.e., general health, physical health complaints, mental health complaints, strain) wellbeing outcomes. The positive relationship between HPWPs and employee wellbeing is weaker the more employees experience leadership behavior in terms of staff care. Thus, our results provide further evidence for a substitutive or compensatory effect between HRM and leadership.